Melhoria no desempenho organizacional de uma empresa de bens de capital usando o Balanced Scorecard: um estudo de caso - Marçola, Jadilson Astorino (Universidade Federal de São Carlos, 2011)
This paper aims to verify if there was improvement in the Performance Management of an organization that uses for more than five years a Performance Management System, denominated Balanced Scorecard. It's necessary to verify if the use of the Balanced Scorecard in this period of time, improved the management system of the organization, transforming the strategy into several operational execution processes. The development of this investigation was grounded in bibliographic references, to identify and evaluate the whole process of Strategy, Planning and Performance Measurement System, as well the involvement of all the stakeholders.
Keywords: Sistemas de medição de desempenho; Estratégia; Planejamento estratégico; Balanced scorecard; Strategy; Strategic planning; Performance measurement system; Balanced scorecard; ENGENHARIAS::ENGENHARIA DE PRODUCAO